PENGUATAN JIWA KEWIRAUSAHAAN MELALUI KESADARAN POTENSI DIRI ANGGOTA BUMDES BERKAH BERSAMA DESA KARANG BUNGA KECAMATAN MANDASTANA KABUPATEN BARITO KUALA - Titien Agustina; Rezti Rezti; Muhammad Nurdin; Sampurnawati Sampurnawati; Sri Suryani; Dodik Jatmika; Syamsuddinnor Syamsuddinnor; Asnawi Asnawi; Alfiannor Alfiannor; Nor Anisa; Maulana Maulana; Auni Humaira Puteri; Soraya Nur Amelia; Muhammad Zaini; Yogi Aris Ardianto (Yayasan Education and Social Center, 2021)
This activity aims to inspire the growth of self-awareness that the potential that God gives to everyone and the natural environment around them is a peerless gift. When moved, used, and empowered will become a new force. The method used is action research or Participatory Action Research (PAR). The object of obstetrics is the caretaker and bumdes members are resources that have real power in spearheading village development. This community service activity is a workshop and focus group discussion (FGD). It is expected to explore the problems faced, obstacles that hinder the progress of themselves and the environment, and solutions that can be given based on real problems faced by the village community. It is hoped that through strengthening awareness of self-potential and environmental wealth will be able to be a driver of the growth of a strong entrepreneurial spirit in the village community. The results of the activities of dialogue and inventory of problems show that the mindset of the village community is still difficult to change with just one activity. Further activities and mentoring are needed that can open new awareness and drive changes in people's mindsets in order to be able to compete